2022
DOI: 10.1155/2022/2844880
|View full text |Cite
|
Sign up to set email alerts
|

Antioxidant, Antidiabetic, and Antibacterial Potentials and Chemical Composition of Salvia officinalis and Mentha suaveolens Grown Wild in Morocco

Abstract: This work evaluated in vitro antioxidant, antidiabetic, and antibacterial properties of Salvia officinalis (S. officinalis) and Mentha suaveolens (M. suaveolens) essential oils (EO). The EOs were extracted, and their chemical composition was determined using GC-MS analysis. The in vitro antioxidant, antidiabetic, and antibacterial activities of S. officinalis and M. suaveolens EO were shown to be remarkable. Furthermore, S. officinalis EO demonstrated better antioxidant findings (using DPPH, ABTS, and FRAP tes… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
22
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 28 publications
(24 citation statements)
references
References 60 publications
1
22
0
1
Order By: Relevance
“…The disc diffusion assay was utilized to evaluate the extract’s initial antimicrobial activity against the selected microbial strains, including a Gram-positive bacterium ( Staphylococcus aureus ATCC BAA 1026) and a Gram-negative bacterium ( Escherichia coli ATCC 9637). The Kirby–Bauer disc diffusion susceptibility protocol was used with minor modifications [ 52 ]. Briefly, the aqueous crude extract was reconstituted in sterile distilled water to obtain a concentration of 100 mg/mL.…”
Section: Methodsmentioning
confidence: 99%
“…The disc diffusion assay was utilized to evaluate the extract’s initial antimicrobial activity against the selected microbial strains, including a Gram-positive bacterium ( Staphylococcus aureus ATCC BAA 1026) and a Gram-negative bacterium ( Escherichia coli ATCC 9637). The Kirby–Bauer disc diffusion susceptibility protocol was used with minor modifications [ 52 ]. Briefly, the aqueous crude extract was reconstituted in sterile distilled water to obtain a concentration of 100 mg/mL.…”
Section: Methodsmentioning
confidence: 99%
“…In the 18th century, it was commonly used as a medicinal herb [ 71 , 72 ]. Various health benefits of Mentha species have been reported [ 50 , 64 ]. Mentha species have shown analgesic activity during in vivo experiments on mice [ 61 ].…”
Section: Health Benefits Of Menthamentioning
confidence: 99%
“…Essential oils of M . suaveolens were found to be very active against α-glucosidase and α-amylase, indicating an inhibitory potential of IC 50 141.16 ± 0.2 and 94.30 ± 0.06 μg/mL, respectively [ 64 ]. Bayani et al [ 98 ] reported on the antidiabetic effect of aqueous extract prepared from M. spicata leaves.…”
Section: Biological Activities Of Menthamentioning
confidence: 99%
“…In this context, natural resources, in particular the molecules contained in medicinal plants, have shown important biological effects, including antioxidant, antidiabetic, and anti-inflammatory activities [ 12 , 13 ]. Among the medicinal plants most used in traditional medicine in Morocco, we find Mentha Piperita ( M. piperita ), commonly known as peppermint.…”
Section: Introductionmentioning
confidence: 99%
“…This plant variety is extensively cultivated for preparing herbal teas and tinctures, or for the management of different conditions and disorders including bowel colic, hepatic disorders, gastritis, headaches, and jaundice [ 15 ]. It has shown several biological effects, such as antioxidant and antidiabetic activity [ 12 , 16 ], as well as insecticidal, antibacterial, antiviral, immunomodulatory, antitumor, neuroprotective, antiallergenic, antifatigue, and cytotoxic activities [ 14 , 17 ]. Peppermint as an essential oil for inhalation is effective in relieving symptoms such as vomiting, nausea, and anorexia in patients undergoing chemotherapy [ 18 ].…”
Section: Introductionmentioning
confidence: 99%